2021
DOI: 10.1186/s13690-021-00711-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of Anemia among pregnant women in sub-Saharan Africa: a systematic review and Meta-analysis

Abstract: Background Anemia is one of the world’s leading cause of disability and the most serious global public health issues. This systematic review and meta-analysis was carried out very prudently in order to give up the pooled prevalence and determinants of anemia in Sub-Saharan Africa. Methodology To carry out this ephemeral systematic review and meta-analysis, a correlated literature review was done from various sources, PubMed Medline and Google Schol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
9
26
1
Order By: Relevance
“…However, the study noted a significant relationship between the knowledge of the benefits of IFAS and the IFAS compliance status of pregnant women. Similar findings established that adherence to IFAS supplementation among pregnant women in Sub-Saharan Africa is not influenced by their income levels or levels of education (Fite et al, 2021). However, in contrast to these findings, research in Kiambu found that the education level of pregnant women did influence their compliance with IFAS in Kiambu County, Kenya (Kamau et al, 2018).…”
Section: Table 3: Association Between Ifas Compliance Status and Some...supporting
confidence: 54%
“…However, the study noted a significant relationship between the knowledge of the benefits of IFAS and the IFAS compliance status of pregnant women. Similar findings established that adherence to IFAS supplementation among pregnant women in Sub-Saharan Africa is not influenced by their income levels or levels of education (Fite et al, 2021). However, in contrast to these findings, research in Kiambu found that the education level of pregnant women did influence their compliance with IFAS in Kiambu County, Kenya (Kamau et al, 2018).…”
Section: Table 3: Association Between Ifas Compliance Status and Some...supporting
confidence: 54%
“…To our knowledge, this is the largest series of pregnant women to examine the impact of maternal anaemia at delivery on adverse maternal and foetal outcomes in the Sub-Saharan Africa region. The prevalence of anaemia at delivery was alarmingly high at 64.8%, representing the second highest rate across all African countries, after that reported from the Republic of Benin (68.2%) [ 7 ], a relatively small west African country with a smaller population as compared with Somalia (≈13 vs 17 million). In Somalia, the prevalence of anaemia among pregnant women was reported to be 49% by the World Bank report 2019 ( https://data.worldbank.org/indicator/SH.PRG.ANEM?locations=SO ).…”
Section: Discussionmentioning
confidence: 99%
“…For PPH detection, the healthcare providers across three countries mostly followed the blood loss threshold of ≥500 ml (and ≥1,000 ml for severe PPH) through visual estimation and assessment of vital signs recommended in international PPH guidelines (5, 10). However, we also found that participants questioned the applicability of the blood loss threshold (≥500 ml) for all women, particularly in sub-Saharan Africa with its' high prevalence of women with anaemia (50). These findings suggest that existing guidelines concerning blood loss thresholds for PPH detection and management may need context-specific adaptations (14,51), with more attention to Hb measurements during pregnancy and on admission in labour to enhance risk assessment.…”
Section: Intravenous Fluidsmentioning
confidence: 84%